2018
DOI: 10.1177/1715163518779409
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions and use of natural health products

Abstract: Most respondents take 1 or more NHPs, preferring to use NHPs over prescription medications for minor and chronic health concerns seemingly based on a perception of safety and quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 16 publications
0
41
1
1
Order By: Relevance
“…The finding that male-identifying participants are significantly more likely to use DS mirrors the results of some studies on post-secondary students [ 12 , 29 ] but not others who reported higher rates of DS use among females [ 13 ]. It also contrasts with the results from recent studies on the general North American population, which found that females are more likely to use DS [ 7 , 11 , 18 , 38 ]. However, this finding should be interpreted with caution as this study had a very low male participation rate.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The finding that male-identifying participants are significantly more likely to use DS mirrors the results of some studies on post-secondary students [ 12 , 29 ] but not others who reported higher rates of DS use among females [ 13 ]. It also contrasts with the results from recent studies on the general North American population, which found that females are more likely to use DS [ 7 , 11 , 18 , 38 ]. However, this finding should be interpreted with caution as this study had a very low male participation rate.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to the Canadian general population, the most commonly consumed type of DS in this study was vitamin/mineral supplements [ 7 , 18 , 28 ]. Alongside vitamins and minerals, this sample also indicated high levels of protein supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study confirmed the results of this study and reported the popularity of the use of ginger, onion and garlic among the general population and the belief in their ability to increase the immunity and reduce the chance of developing COVID-19. Previous studies reported that there is a common belief that herbal products are safer than prescription medications and of good quality ( Barry, 2018 , El Khoury et al, 2016 ). Dissatisfaction with conventional therapy, good experiences, with previously used herbal medicine, as well as family traditions and habits were commonly-reported reasons for the use of herbal products and supplements ( Welz, Emberger-Klein, and Menrad 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dissatisfaction with conventional therapy, good experiences, with previously used herbal medicine, as well as family traditions and habits were commonly-reported reasons for the use of herbal products and supplements ( Welz, Emberger-Klein, and Menrad 2018 ). Vitamin C is one of the most commonly used vitamin across different populations due to its ability to contributes to immune defense by supporting various cellular functions of both the innate and adaptive immune system ( El Khoury et al, 2016 , Barry, 2018 , Carr and Maggini, 2017 ). In addition, vitamin C supports epithelial barrier function, promotes the oxidant scavenging activity, accumulates in phagocytic cells (such as neutrophils) and stimulate various defense mechanisms that contribute ultimately microbial killing ( Carr and Maggini 2017 ).…”
Section: Discussionmentioning
confidence: 99%